THE IMPACT OF REGIONAL EXPLANATION ON PUBLIC SERVICES BASED ON INDONESIAN LEGAL SYSTEM - Ali Abu Bakar; Siti Mawar; Nurdin Syah (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2018)
Region expansion is one of the main keys in providing services to the community, after the establishment of Law Number 22 of the Year 1999 concerning the regional government. This law was established due to problems arose mainly concerning the lack of public services, the extent of territory, territorial borders, ethnic and cultural differences, and unfair development in all regions and others, leading to many problems in the community. The results of this study revealed that region expansion had positive implications in term of social, political and cultural recognition of regional communities. Through the expansion policy, community entities with a long history of cohesiveness and greatness have been recognized as new autonomous regions. This recognition has, in turn, positively contribute to community satisfaction, which ultimately increases the regional support for central governments. It can be concluded that regional expansion policies shorten the geographical distance between citizen settlements and service centers, and narrow the range of control between the local governments and its lower government units. In addition, the expansion enables the government to bring new types of service to the area, such as electricity, water, and health services. Abstrak: Pemekaran daerah merupakan salah satu kunci utama dalam memberikan pelayanan kepada masyarakat, setelah disahkannya atas UU No. 22 Tahun 1999 tentang pemerintahan daerah, lahirnya undang-undang ini dikarenakan adanya permasalahan-permasalahan yang timbul terutama dari segi kurangnya pelayanan publik, luasnya wilayah, batas wilayah, perbedaan suku dan budaya,dan pembangunan yang tidak merata di seluruh daerah dan lain-lain, sehingga menimbulkan banyak permasalahan dalam masyarakat. Hasil penelitian ini menemukan bahwa pemekaran daerah membawa implikasi positif dalam bentuk pengakuan sosial, politik dan kultural masyarakat daerah. Melalui kebijakan pemekaran, entitas masyarakat yang mempunyai sejarah kohesivitas dan kebesaran yang panjang, memperoleh pengakuan sebagai daerah otonom baru. Pengakuan ini pada gilirannya memberikan kontribusi positif terhadap kepuasan masyarakat, sehingga meningkatkan dukungan daerah terhadap pemerintah nasional. Intisari kesimpulan yang dapat diambil adalah Kebijakan pemekaran daerah mampu memperpendek jarak geografis antara pemukiman penduduk dengan sentra pelayanan, juga mempersempit rentang kendali antara pemerintah daerah dengan unit pemerintahan di bawahnya. Disamping itu, pemekaran juga memungkinkan untuk menghadirkan jenis-jenis pelayan baru di Daerah tersebut seperti pelayanan listrik, Air, Kesehatan dan sebagainya. Kata Kunci: Dampak Pemekaran, Pelayanan Publik, Otonomi Khusus